Computer–controlled non–steady–state engine testing. (4th August 2014) - Godburn, J.R.; Brown, D.G.; Case, R.
A programme of dynamic testing of automotive engines on a dynamometer is described. The engines were subjected to varying rates of acceleration and deceleration under computer control. Data from fast–response instrumentation was logged by the computer, processed and output in the form of conventional performance characteristic curves. These are compared with conventionally obtained curves, and it is concluded that with appropriate instrumentation, speed ramp rates and statistical processing of data, accurate performance curves can be obtained very rapidly.